ANALISIS TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA (Studi Kasus Pada Kantor Desa LalongKecamatan Wae Rii Kabupaten Manggarai Tengah) - Departo, Maria Firayani E; Soleiman, Iriany Dewi; Thalib, Sabra B Wahab (Program Studi Akuntansi Universitas Flores, 2024)
The purpose of this study is to determine the transparency and accountability of village financial management. The method used in this research is descriptive qualitative. Data collection techniques used are observation, interviews, documentation, literature study. Data analysis techniques through data collection, data reduction, drawing conclusions. The results of the analysis carried out by researchers regarding Transparency in Lalong Village are not in accordance with Minister of Home Affairs Regulation Number 113 of 2014 article 40. And there are deficiencies because they are not in accordance with the results of observations made by researchers where there is no access that allows the community to find out about village financial management or in terms of transparency, it is not permissible to view detailed APBDesa reports. The results of the analysis regarding the Accountability of Financial Management in Lalong Village conducted by researchers, that starting from the planning, implementation, administration, reporting and accountability stages have used indicators in accordance with Minister of Home Affairs Regulation Number 113 of 2014 article 40. However, some are not in accordance with the observations made carried out by researchers, namely the absence of media as a form of village government accountability regarding village financial management.